2010
DOI: 10.1007/s10643-010-0420-2
|View full text |Cite
|
Sign up to set email alerts
|

Family Child Care Providers’ Perspectives Regarding Effective Professional Development and Their Role in the Child Care System: A Qualitative Study

Abstract: This study examines family child care providers' perspectives regarding effective professional development and their role in the early learning and care system. Four focus groups were conducted annually for 3 years involving a total of 54 licensed family child care providers. Supportive social relationships emerged as an important dimension of family child care providers' professional development experience. Providers preferred a cohort design which enabled them to establish relationships with colleagues and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 13 publications
2
51
0
Order By: Relevance
“…Higher measured structural and process quality found among the preschool classrooms in the current study with more structural quality requirements may have been caused by the higher standards. The higher structural requirements and related higher measured structural quality feature of teacher education and physical space may have strengthened process quality features of environmental design and activities in those classrooms, consistent with prior research on teacher education and process quality (Burchinal et al, 2002; Clarke-Stewart et al, 2002; Cryer et al, 2003; Lanigan, 2011; Phillips, Mekos, Scarr, McCartney, & Abbott-Shim, 2000; Phillipsen et al, 1997; Raikes et al, 2005). The current study, however, was non-experimental and cause could not be investigated nor concluded.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Higher measured structural and process quality found among the preschool classrooms in the current study with more structural quality requirements may have been caused by the higher standards. The higher structural requirements and related higher measured structural quality feature of teacher education and physical space may have strengthened process quality features of environmental design and activities in those classrooms, consistent with prior research on teacher education and process quality (Burchinal et al, 2002; Clarke-Stewart et al, 2002; Cryer et al, 2003; Lanigan, 2011; Phillips, Mekos, Scarr, McCartney, & Abbott-Shim, 2000; Phillipsen et al, 1997; Raikes et al, 2005). The current study, however, was non-experimental and cause could not be investigated nor concluded.…”
Section: Discussionsupporting
confidence: 79%
“…Teacher education plays a vital role in process quality with teachers’ training influencing the child skill development and experiences they are able to provide for children in their classrooms (Burchinal, Howes, & Kontos, 2002; Clarke-Stewart, Vandell, Burchinal, O’Brien, & McCartney, 2002; Cryer et al, 1999; Lanigan, 2011; Raikes, Raikes, & Wilcox, 2005). The transition to a more highly trained staff in preschool classrooms has been stimulated by the Improving Head Start for School Readiness Act of 2007, which requires at least 50% of Head Start lead teachers to have bachelor’s or advanced degrees in early childhood education or related fields (Head Start, 2007).…”
mentioning
confidence: 99%
“…Prior research on FCC providers finds that many providers experience isolation from other colleagues, early childhood resources, and supports (Bromer and Pick 2012;Drake et al 2006;Lanigan 2011;Porter et al 2010). As a result, it is not surprising that providers across studies report interest in opportunities for social and peer support and networking with other child care providers (Lanigan 2011;Liu and Anderson 2010;Rusby 2002;Shivers 2008).…”
Section: Provider Experiences With Training and Supportmentioning
confidence: 99%
“…Prior research on FCC providers finds that many providers experience isolation from other colleagues, early childhood resources, and supports (Bromer and Pick 2012;Drake et al 2006;Lanigan 2011;Porter et al 2010). As a result, it is not surprising that providers across studies report interest in opportunities for social and peer support and networking with other child care providers (Lanigan 2011;Liu and Anderson 2010;Rusby 2002;Shivers 2008). In a qualitative examination of FCC provider participation in one state's professional development system over a threeyear time period, providers reported that ongoing cohort-based training was beneficial and that the opportunity to develop a trusting supportive relationship with a facilitator and other providers helped to reduce their experiences of isolation and marginalization (Lanigan 2011).…”
Section: Provider Experiences With Training and Supportmentioning
confidence: 99%
See 1 more Smart Citation